2020
DOI: 10.1080/17516234.2020.1845472
|View full text |Cite
|
Sign up to set email alerts
|

Social entrepreneurship in context: pathways for new contributions in the field

Abstract: In this Special Issue, we hope to reframe the conversation about context and bring back context to the front and centre of our way of knowing and theorizing in the field of social entrepreneurship. We philosophize about context and then propose a typology of context in the field of social entrepreneurship (broadly defined) and identify domains of context that constitute existing and fertile areas for future research. We reflect on the six papers in this special issue in relation to our context typology and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 100 publications
0
14
0
1
Order By: Relevance
“…The research contributes to the investigation of social entrepreneurship in Georgia, as previous studies have suggested exploring the phenomenon in different countries, contexts, and economies (e.g., Cagarman et al 2020;Chandra and Kerlin 2020). It also provides insight and a better understanding of social entrepreneurship as an important research field and as a discipline (Cieslik 2018;Mair and Martí 2006).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The research contributes to the investigation of social entrepreneurship in Georgia, as previous studies have suggested exploring the phenomenon in different countries, contexts, and economies (e.g., Cagarman et al 2020;Chandra and Kerlin 2020). It also provides insight and a better understanding of social entrepreneurship as an important research field and as a discipline (Cieslik 2018;Mair and Martí 2006).…”
Section: Discussionmentioning
confidence: 80%
“…A country context plays a central role in the research of social entrepreneurship, but the literature deals mainly with the North American, Asian, and European countries relating to social entrepreneurial theory, practice, data, and perspectives (Li 2019;Chandra and Kerlin 2020;Li et al 2020). Therefore, conducting a study in different contexts is significant for the discipline.…”
Section: Introductionmentioning
confidence: 99%
“…Context matters for the specific manifestation of managerial practices of nonprofits (cf. Chandra & Kerlin, 2020), but the fundamental public management drivers of these practices (Brown & Potoski, 2004;Eikenberry & Kluver, 2004;Van Slyke, 2006;Jing, 2018) are strikingly universal across the very different contexts of China and the Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…Contexts can be characterized in terms of their political-administrative system, such as: concentration of power, administrative capacity, or level of (de)centralization (Meier, Rutherford & Avellaneda, 2017;Pollitt & Bouckaert, 2017). Contexts in the field of social entrepreneurship include characteristics of culture (e.g., religiosity and tradition), socio-economic characteristics, and domain-specific characteristics (Chandra & Kerlin, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation